1993
DOI: 10.1079/bjn19930049
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal responses of rats fed on white and wholemeal breads: complex carbohydrate digestibility and the influence of dietary fat content

Abstract: To obtain quantitative information on the digestibility of the non-starch polysaccharides (NSP) fraction of white and wholemeal breads, rats were fed on diets in which freeze-dried bread (white, wholemeal or mixtures of the two) provided all the complex carbohydrates. In a second experiment the possibility that dietary fat concentration might influence NSP digestibility was tested by feeding diets containing 30 or 170 g maize oil/kg and either white or wholemeal bread. Multiple linear regression analysis provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
4
11
2
Order By: Relevance
“…Approximately 100 % disappearance of guar gum within the alimentary tracts of rats and human subjects has been reported (Nyman et al 1986), but to our knowledge the present study is the first study that has attempted to determine the effect of an oral dose of guar gum (or sodium alginate) on digestibility of the NSP in the hydrocolloid. In contrast to earlier studies in which peas (Pisum sativum); bread and beans (Phaseolus vulgaris) were fed to rats at a range of doses and where there was little evidence of a diminution in digestibility of NSP with higher intakes (Goodlad & Mathers, 1990Key & Mathers, 1993a,b, 1995, the present study provided clear evidence that with 100 g NSP source/kg diet, there was significantly P , 0´001 reduced whole-gut NSP digestibility (Fig. 1).…”
Section: Fate Of Nsp Sources In the Gutcontrasting
confidence: 99%
See 1 more Smart Citation
“…Approximately 100 % disappearance of guar gum within the alimentary tracts of rats and human subjects has been reported (Nyman et al 1986), but to our knowledge the present study is the first study that has attempted to determine the effect of an oral dose of guar gum (or sodium alginate) on digestibility of the NSP in the hydrocolloid. In contrast to earlier studies in which peas (Pisum sativum); bread and beans (Phaseolus vulgaris) were fed to rats at a range of doses and where there was little evidence of a diminution in digestibility of NSP with higher intakes (Goodlad & Mathers, 1990Key & Mathers, 1993a,b, 1995, the present study provided clear evidence that with 100 g NSP source/kg diet, there was significantly P , 0´001 reduced whole-gut NSP digestibility (Fig. 1).…”
Section: Fate Of Nsp Sources In the Gutcontrasting
confidence: 99%
“…The reason for the reduced NSP digestibility with the higher NSP intake was not established, but may be associated with inadequate time for bacterial hydrolysis of the test polymers, since alterations in gut transit time has a strong influence on extent of NSP digestion (Mathers, 1991). There was a strong linear increase in faecal N output with increasing consumption of GG and SA, which is consistent with previous observations in rats fed increasing levels of dietary NSP (for example, see Goodlad & Mathers, 1990;Key & Mathers, 1993a). It has been suggested that increased faecal N output may be due to enhanced loss of endogenous N arising from stimulation of mucosal cell turnover (Skurpakkar et al 1979).…”
Section: Fate Of Nsp Sources In the Gutsupporting
confidence: 86%
“…Possible interactions between UCC and dietary fat affecting faecal energy losses are being studied in man (P. Moe, USDA Human Nutrition Laboratory). Key & Mathers (1992) showed that increasing maize oil from 30 to 170 g/kg diet in rats fed either white or wholemeal bread appeared not to influence NSP digestibility, so effects of fat on the energy values of NSP would not be predicted.…”
Section: Losses O F E N E R G Y D U E To F E R M E N T a T I O N Prodmentioning
confidence: 99%
“…In human diets, RS and NSP coexist, but little is known about the effects of NSP on the fermentation of RS. Key and Mathers21 and Young and colleagues15 found that insoluble NSP increased faecal starch excretion in rats. In addition, the latter group showed that the enhanced tumorigenesis in the distal colon by RS was suppressed by adding wheat bran to the diet.…”
mentioning
confidence: 99%